(untitled) (Western European Journal of Historical Events and Social Science, 2025)
The article focuses on the impact of cinema on individual spirituality and the analysis of its social functions. In modern society, the consequences of increasing factors affecting personality spirituality, subordination of cinema to market relations are studied. It has been analyzed that cinema, like all types of art, performs certain social functions, the existence of identities and differences between them.